Respon beberapa Varietas Padi terhadap Stress Garam - Sugiyono Sugiyono; Siti Samiyarsih (Fakultas Biologi | Universitas Jenderal Soedirman, 2005)
A study on the Responses of Several Rice Varieties toward Salt Stress has been carried out with a view to: 1) study the effect of salt stress on the physiological and anatomical responses of several rice varieties; 2) determine salt tolerant rice variety(ies). Research results showed that there were both physiological and anatomical changes on salt-stressed rice. Those changes were determined by the level of salt concentration given. The higher the concentration the more obvious the changes appeared. There was a dramatic decrease in the total chlorophyll content of the salt-stressed leaf, coupled by a sharp decrease in the chlorophyll a/b ratio. Salt stress also resulted in the decrease in mesophyll thickness, and in turn leads to the decrease of leaf’s length and width. In general, salt stress resulted in the decrease of plant growth, as indicated by the decrease of plant’s fresh and dry weights, eventual plant’s death was therefore imminent. The rice varieties used were sensitive to salt stress since an exposure of 50 mM NaCl has already resulted in the interference of rice growth.